Molecular dynamics of amorphous pharmaceutical fenofibrate studied by broadband dielectric spectroscopy - U. Sailaja; M. Shahin Thayyil; N.S. Krishna Kumar; G. Govindaraj (Elsevier, 2016)
Fenofibrate is mainly used to reduce cholesterol level in patients at risk of cardiovascular disease. Thermal transition study with the help of differential scanning calorimetry (DSC) shows that the aforesaid active pharmaceutical ingredient (API) is a good glass former. Based on our DSC study, the molecular dynamics of this API has been carried out by broadband dielectric spectroscopy (BDS) covering wide temperature and frequency ranges. Dielectric measurements of amorphous fenofibrate were performed after its vitrification by fast cooling from a few degrees above the melting point (Tm=354.11 K) to deep glassy state. The sample does not show any crystallization tendency during cooling and reaches the glassy state. The temperature dependence of the structural relaxation has been fitted by single Vogel-Fulcher-Tamman (VFT) equation. From VFT fit, glass transition temperature (Tg) was estimated as 250.56 K and fragility (m) was determined as 94.02. This drug is classified as a fragile glass former. Deviations of experimental data from Kohlrausch-Williams-Watts (KWW) fits on high-frequency flank of α-peak indicate the presence of an excess wing in fenofibrate. Based on Ngai׳s coupling model, we identified the excess wing as true Johari-Goldstein (JG) process. Below the glass transition temperature one can clearly see a secondary relaxation (γ) with an activation energy of 32.67 kJ/mol.